PROBLEMATIKA PENERAPAN PEMBELAJARAN MAHFÛZHAT BAHASA ARAB BAGI MAHASISWA - Abdurrahman, Maman; Masor, Masor; Maulani, Hikmah; Kartini, Ade (Arabi : Journal of Arabic Studies, 2020)
Characteristic of mahfuzhat is using of high register and contain cultural content and norms. That is bring  own problems into student from memorizing procces, understanding a meaning and practicing. The goals of this study aims to describe and to provide a solution problematic that it has related with mahfuzhat learning. This research uses a case study approach, by observing field phenomena. As for the research subjects, namely students of the 1st semester of the Arabic Language Education Department. The data were collected using observation, interviews, and documentation, then the data analysis used was data display, data reduction and triangulation. The research findings show that the problem of competency aspects is due to aspects of vocabulary, rules and differences in several elements and characteristics between Arabic and Indonesian, the lack of time for practice, non-linguistic problems due to internal and external factors of the learners. The solutions include increasing the components and implementing learning as well as strengthening the motivation and self-confidence of learner.